2013
DOI: 10.1155/2013/684736
|View full text |Cite
|
Sign up to set email alerts
|

Review of Signaling Pathways Governing MSC Osteogenic and Adipogenic Differentiation

Abstract: Mesenchymal stem cells (MSC) are multipotent cells, functioning as precursors to a variety of cell types including adipocytes, osteoblasts, and chondrocytes. Between osteogenic and adipogenic lineage commitment and differentiation, a theoretical inverse relationship exists, such that differentiation towards an osteoblast phenotype occurs at the expense of an adipocytic phenotype. This balance is regulated by numerous, intersecting signaling pathways that converge on the regulation of two main transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
399
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(425 citation statements)
references
References 223 publications
7
399
1
11
Order By: Relevance
“…It is likely that NF-kB regulates osteogenesis in a Runx2-independent pathway, such as by b-catenin signaling. 36 In other studies, the suppression of NF-kB promoted osteogenesis in primary bone marrow-derived MSCs and conditional NF-kB-deficient mice. 31 The suppressive effects of NF-kB on osteogenesis are mediated by direct upregulation of Smurf1/2 expression to enhance b-catenin degradation.…”
Section: Figmentioning
confidence: 91%
“…It is likely that NF-kB regulates osteogenesis in a Runx2-independent pathway, such as by b-catenin signaling. 36 In other studies, the suppression of NF-kB promoted osteogenesis in primary bone marrow-derived MSCs and conditional NF-kB-deficient mice. 31 The suppressive effects of NF-kB on osteogenesis are mediated by direct upregulation of Smurf1/2 expression to enhance b-catenin degradation.…”
Section: Figmentioning
confidence: 91%
“…Bone morphogenetic proteins (BMPs) are extracellular cytokines originally isolated from bone extracts and have been found to induce ectopic chondrogenesis and osteoblastogenesis 6. It has been reported that the BMP‐2, BMP‐4, BMP‐6, BMP‐7, and BMP‐9 subtypes promote osteogenic commitment, as well as terminal osteogenic differentiation in MSCs 7.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the BMP‐2, BMP‐4, BMP‐6, BMP‐7, and BMP‐9 subtypes promote osteogenic commitment, as well as terminal osteogenic differentiation in MSCs 7. Additionally, recombinant human BMP‐2 and BMP‐7 have been clinically applied in various bone disorders 6. However, it has also been demonstrated that BMPs have pro‐adipogenic effects 8.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MSCs can serve as precursors to a variety of mature mesenchymal cell types, including osteoblasts, chondrocytes, myocytes, and many other types of cells (James, 2013). It is important to notice that with the progressive differentiation toward a mature cell phenotype, often the capacity for differentiation into a competing lineage is lost.…”
Section: Introductionmentioning
confidence: 99%